THE JUSTICE ASPECT OF JUDICIAL CONSIDERATIONS ON THE FULFILLMENT OF VICTIMS’ RIGHTS IN PAST ACTS OF TERRORISM - Rizky Kurnia; Prija Djatmika; Milda Istiqomah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Constitutional Court Decision Number 103/PUU-XXI/2023 marks a pivotal turning point in the protection of the rights of victims of terrorism, particularly those affected prior to the enactment of Law Number 5 of 2018, who have not yet received adequate legal protection. This paper analyzes the aspect of justice considered by the Constitutional Court judges in fulfilling the rights of past victims of terrorism as reflected in Decision Number 103/PUU-XXI/2023, as well as the conceptual framework for the realization of such rights within the Indonesian criminal justice system. The findings of this study reveal that the element of justice in the Court's reasoning is embodied in a substantive and humanistic approach, which reinforces the state's responsibility to fulfill the constitutional rights of victims of past terrorism acts as a manifestation of human rights protection and the principle of equality before the law. The ideal concept of fulfilling the rights of victims of past acts of terrorism emphasizes restorative justice through recognition, protection, and recovery, supported by a comprehensive legal framework and equitable, implementable policies.